Edukasi Pencegahan Gizi Buruk Pada Ibu Balita dan Kader Posyandu di Desa Kajar Kabupaten Bondowoso - Lirista Dyah Ayu Oktafiani; Dewi Rokhmah; Khoiron Khoiron; Zuwina Eka Puspita Arini; Agnes Candrika Trisna Maharani; Arif Ikhwan Hanafi; Fani Lailatul Rochmah; Fatimatus Sahro; Ricta Huniana Pratiwi; Annisa Nur Mahmudah; Annisa’ Kholifatu Qurrota A’yun; Sephiana Diah Anggraini; Poutry Dhewy Roushita Shary (Indonesian Journal Publisher, 2024)
Malnutrition is known to be a health problem that has not been completely addressed, so serious intervention and treatment is needed because it is irreversible or cannot be returned (Lang, 2023). Based on data from the 2022 Nutrition Status Survey (SSGI), Bondowoso Regency is one of the districts that has a fairly high prevalence of children under five with malnutrition, namely 7.7%. This activity aims to prevent and treat malnutrition among toddlers in Kajar Village, Bondowoso Regency. This activity was carried out using the lecture method using PowerPoint and demonstration media. The results of the activity showed that there was an increase in mothers' knowledge regarding the use of local functional food ingredients. Based on the results of the pretest and posttest, the average value of the pretest and posttest increased knowledge from 67.50 to 80.50. Based on the results of the pretest and posttest, it shows that there was a significant increase in this activity by 13% from 66.5% (pretest) to 79.5% (posttest). It can be concluded that the intervention carried out using lecture and demonstration methods was effective in increasing the knowledge of mothers of toddlers.